Digital Inclusive Finance, Entrepreneurial Activity of Farmers, and Urban–Rural Income Disparity: Evidence from China - Le, Xiaobing; Aralas, Sarma Binti (Organizations and Markets in Emerging Economies, 2025)
In recent years, although the ratio of urban to rural per capita income in China has exhibited a continuous downward trend, the income gap between urban and rural areas remains significantly higher than that of developed countries. Addressing this inequality and achieving common prosperity has become one of the key objectives of national development. Utilizing a sample from mainland China, this paper empirically analyzes the role of digital inclusive finance in narrowing the urban–rural income gap by employing the Theil index to assess this disparity. The findings indicate that digital inclusive finance significantly alleviates the urban–rural income gap; however, its impact varies across different dimensions and regions. Furthermore, threshold effect analysis reveals a non-linear relationship between digital financial inclusion and the urban–rural income gap, with farmers’ entrepreneurial activities serving as an important moderating factor in this process. The results of this paper provide new insights into the understanding of urban–rural income distribution issues and offer valuable policy recommendations for addressing imbalances in urban–rural development.